18F-PBR06 PET/CT imaging for evaluating atherosclerotic plaques linked to macrophage infiltration. Issue 4 (April 2019) - Zhang, He; Xiao, Jie; Zhou, Jun; Tan, Hui; Hu, Yan; Mao, Wujian; Fu, Zhequan; Lin, Qingyu; Shi, Hongcheng; Cheng, Dengfeng
Abstract : Background: The present study explored the 18 kDa translocator protein radioligand [ 18 F]N-fluoroacetyl-N-(2, 5-dimethoxybenzyl)-2-phenoxyaniline ( 18 F-PBR06) targeting macrophages for PET imaging of atherosclerotic plaques and evaluating the vulnerability of atherosclerotic plaques toward rupture. Materials and methods: 18 F-PBR06 was synthesized using a Synthra RNplus module automatically. RAW264.7 cells were used for cell binding study with 18 F-PBR06. In-vivo micro-PET/CT imaging for ApoE −/− mice and C57 mice was performed 1 h after injection of 18 F-PBR06. CD68 + and F480 immunofluorescence stainings were performed in the aorta tissues. Results: In-vitro cell studies showed uptake of 18 F-PBR06 to RAW264.7 cells. Micro-PET/CT imaging identified the atherosclerotic lesions in the aortic arch of ApoE −/− mice successfully, whereas no signal was observed in C57 mice. The ratio of plaque-to-muscle in ApoE −/− mice of 32 weeks was significantly higher than that in ApoE −/− mice of 22 weeks, which was confirmed by CD68 + immunofluorescence staining and F480 immunofluorescence staining. Conclusion: TSPO radioligand 18 F-PBR06 allows noninvasive PET/CT imaging of macrophage-abundant atherosclerotic plaques as well as positive correlation between PET imagings and ex-vivo immunofluorescence staining of plaques in mice with different ages, thereby representing a potential attractive tool for evaluating the vulnerability of atherosclerotic plaques towards rupture.